2012
DOI: 10.1007/978-3-642-28926-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Incomparability Graphs of Lattices

Abstract: Abstract. Let L be a finite lattice with atleast two atoms and W (L) = {x | there exists y ∈ L such that x y }. The incomparability graph of L, denoted by Γ (L), is a graph with vertex set W (L) and two distinct vertices a, b ∈ W (L) are adjacent if and only if they are incomparable. In this paper, we study the incomparability graphs of lattices. We prove that, a disconnected graph is a graph of a lattice L if and only if L is of the form L1 L2. We prove that, Γ (L) cannot be an n-gon for any n ≥ 5. Some prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Wasadikar and Survase [12] have shown that all connected graphs with at most four vertices can be realized as Γ (L).…”
Section: Some Realizable and Non Realizable Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wasadikar and Survase [12] have shown that all connected graphs with at most four vertices can be realized as Γ (L).…”
Section: Some Realizable and Non Realizable Graphsmentioning
confidence: 99%
“…Wasadikar and Survase [12] introduced the incomparability graph of a lattice. Throughout this paper, L is a finite lattice with at least two atoms.…”
Section: Introductionmentioning
confidence: 99%